Evaluation of optical 3D scanning system for radiotherapy use. Issue 2 (7th December 2021) - Crowe, Scott; Luscombe, Jenna; Maxwell, Sarah; Simpson‐Page, Emily; Poroa, Tania; Wilks, Rachael; Li, Weizheng; Cleland, Susannah; Chan, Philip; Lin, Charles; Kairn, Tanya
Abstract: Introduction: Optical three‐dimensional scanning devices can produce geometrically accurate, high‐resolution models of patients suitable for clinical use. This article describes the use of a metrology‐grade structured light scanner for the design and production of radiotherapy medical devices and synthetic water‐equivalent computer tomography images. Methods: Following commissioning of the device by scanning objects of known properties, 173 scans were performed on 26 volunteers, with observations of subjects and operators collected. Results: The fit of devices produced using these scans was assessed, and a workflow for the design of complex devices using a treatment planning system was identified. Conclusions: Recommendations are provided on the use of the device within a radiation oncology department. Abstract : Optical three‐dimensional scanning devices can produce geometrically accurate, high‐resolution models of patients. In this study, the potential application of these models in the design of radiotherapy treatments and devices has been explored by acquiring 173 scans of 26 volunteers. This paper provides a summary of observations made by both subjects and operators, and describes a clinical workflow that could be employed in other departments.